Characterising crack growth in commercially pure titanium. (April 2021) - Jones, Rhys; Lang, Jeff; Papyan, Vahram; Peng, Daren; Lua, Jim; Ang, Andrew
Highlights: It reveals that crack growth in Grade 2, 3 and 4 Titanium can be approximated by the same master curve. This master curve representation is R ratio independent. It reveals that for Grade 3 Titanium this representation also holds for a range of different environments. It reveals that this representation is similar to that of AA7050-T7451. The durability analyses suggest that CP Titanium may be attractive for use as replacement parts. Abstract: One of the challenges in aircraft sustainment is to develop additively manufactured (AM) replacement parts for legacy aircraft. This is particularly important for fixed and rotary wing aircraft that operate in in aggressive environments, i.e. off carriers, in a marine environment, etc. On the other hand the United States Air Force (USAF) have now adopted the concept of using AM to rapidly field limited-life unmanned air platforms. Whilst the temptation is to use AM Ti-6Al-4 V for these purposes, Ti-6Al-4 V powder is both costly and its supply is somewhat restricted. This paper reveals that the yield and ultimate strengths, the strain to failure of commercially pure (CP) Titanium, which is highly corrosion resistant, and it's resistance to crack growth is superior to that of the commonly used aluminium ally AA7050-T7451, which is used in the F/A-18 Hornet, Super Hornet and F-35 (Joint Strike Fighter). Interestingly, when allowance is made for these improved properties then, if the crack growth rate da/dN is expressed as per the Hartman-Schijve crack growth equation, the resultant crack growth curves for Grade 2, 3 and 4 Titanium, and AA7050-T7451 all fall onto (essentially) the same master curve. It is also shown that the effect of different aggressive environments on Grade 3 Titanium is merely to change the fatigue threshold and that, when allowance is made for this, the crack growth curves associated with these different environments also fall onto the same master curve determined for CP Titanium and AA7050-T7451 tested in a laboratory air environment. Consequently, the damage tolerance and durability analyses presented in this paper suggest that CP Titanium may be attractive both for use as replacement parts for many aircraft parts, and for unmanned aerial vehicles (UAV's).